Epidemiological Monitoring of Crimean Hemorrhagic Fever Natural Focus in the Volgograd Region in 2000-2009 - V. V. Manankov; V. V. Alekseev; V. P. Smelyanskiy; T. P. Pashanina; N. I. Pogasiy; E. V. Putintseva; A. L. Britanova; V. A. Antonov; V. V. Alekseeva; G. A. Tkachenko; S. T. Savchenko; N. V. Rusakova; et al. (Проблемы особо опасных инфекций, 2010)
104 cases of Crimean hemorrhagic fever (CHF), including 9 lethal (8.6 %) were registered in the Volgograd Region in 2000-2009. Dynamics of human incidence and its association with the level of infection in the main carrier and vector - H. marginatum tick were demonstrated. The expansion of this species habitat resulted in the natural focus borders extension. The data presented in the article allowed to make a conclusion that persistent actively functioning natural focus of CHF had been formed in the territory of the Volgograd Region. The epicenter of this focus is situated in 2 South-Western regions - Kotelnikovsky and Oktyabrsky, - and with neighboring administrative territories and green belt of the Volgograd Southern regions being actively involved in the epidemic process.